The Effectiveness of the Judicial Commission in Upholding Judicial Integrity: Between Expectations and Reality (Indonesian Court and Justice Review, 2025)
The Judicial Commission of Indonesia was established to promote integrity and accountability within the judiciary. Despite its constitutional mandate, the Commission's effectiveness remains a subject of contention. This study investigates the performance of the Judicial Commission in addressing ethical violations, reviewing judicial conduct, and maintaining public trust in the judicial system. Drawing from institutional reports, case data, and expert interviews, the research examines the gap between the Commission’s legal authority and its operational capacity. Findings reveal that while the Commission has received thousands of public complaints, its ability to enforce sanctions is limited by legal ambiguities, resistance from judicial institutions, and restricted investigatory powers. The Constitutional Court’s decisions narrowing the Commission’s authority further weaken its oversight function. The study underscores a persistent mismatch between public expectations and the institutional constraints the Commission faces. The novelty lies in its critical institutional assessment post-reform, highlighting the need to redefine the Commission’s role within the broader judicial governance framework. This study contributes to the discourse on judicial accountability by exploring how independent oversight bodies operate within constrained legal-political environments. It also offers concrete recommendations to enhance the Commission’s legitimacy, legal mandate, and cooperation with the Supreme Court, ensuring a more effective system of judicial discipline in Indonesia.